Sector eléctrico: marco institucional, problemas y nuevas tendencias - Quiñones Alayza, Maria Teresa; Quintanilla Acosta, Edwin (Pontificia Universidad Católica del Perú, 2016)
The power sector of a country is highly relevant for its competitiveness and social development. In Peru, this sector has passed through many changes before having its current configuration, which has negative and positive aspects.In the present versus, two different perspectives come face to face as the debate about key and current topics starts. The discussion is about questions such as the “oversupply” of power generation, the creation of additional charges to the power transmission  service, or the frontiers of the regulated market.

El sector eléctrico de un país es de suma importancia para su competitividad y desarrollo social. En el Perú, este sector ha pasado por varios cambios hasta tener su configuración actual, que tiene aspectos tanto positivos como negativos.En el presente versus, dos diferentes perspectivas se encuentran y se abre paso al debate acerca de temas clave y de actualidad, tales como: la “sobreoferta” de generación eléctrica, la creación de cargos adicionales a la transmisión, o los límites del mercado regulado.
Power sector: institutional framework, issues, and new trends
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01